THE FUNCTIONS, COMPETENCIES, AND ETHICAL RESPONSIBILITIES OF PROFESSIONAL TRANSLATORS IN CONTEMPORARY TRANSLATION PRACTICE (Ustozlar uchun, 2026)
Professional translators occupy a critical position in the contemporary landscape of cross-linguistic and cross-cultural communication. Their work extends beyond the literal conversion of text, encompassing linguistic expertise, cultural mediation, and ethical responsibility. This article examines the functions and competencies of professional translators, highlighting their role in ensuring accuracy, contextual appropriateness, and stylistic fidelity across diverse domains, including literary, technical, legal, and diplomatic translation. The study also addresses the integration of technological tools, such as computer-assisted translation and machine translation post-editing, and emphasizes the evolving responsibilities of translators in a globalized, digitally mediated environment. The findings underscore that professional translators are indispensable agents in the transmission of knowledge, ideas, and cultural values, demonstrating the complexity and significance of their contributions to modern communication.